2016
DOI: 10.3389/fpsyg.2016.01957
|View full text |Cite
|
Sign up to set email alerts
|

Family Digital Literacy Practices and Children’s Mobile Phone Use

Abstract: Smart phones are ubiquitous in everyday life and are having a major impact on work, education, social relationships and modes of communication. Children are the fastest growing population of smart phone users, with use often focusing around internet access, e.g., 1 in 3 internet users in the UK are under 18 years of age. Despite their widespread use, relatively little is known about the factors that underpin children’s use. The home is a significant ecological context of development and recent research has hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 45 publications
0
58
1
9
Order By: Relevance
“… 14 It is also clear that such change of parental behavior has a significant impact on children's media use. 12 There are several suggestions on how this effect is mediated. Although this study did not directly measure parental television use, parents' media use is an important determinant of their children's.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 14 It is also clear that such change of parental behavior has a significant impact on children's media use. 12 There are several suggestions on how this effect is mediated. Although this study did not directly measure parental television use, parents' media use is an important determinant of their children's.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also indicated the necessity for longitudinal or age group-based research. 8 12 Young children's screen use is influenced by various factors; it is more directly dependent on family environment, such as parental guidance, than school-aged children. 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En edad escolar, sobre todo, para juegos, y, al llegar a la adolescencia, evolucionan del uso principalmente lúdico al comunicativo, facilitado por la eclosión de las redes sociales, lo que indica que integran la tecnología en sus hábitos de vida y la utilizan de una forma positiva. 6 Se ha mencionado que el uso de la tecnología, de los videojuegos y de las redes sociales mejora las capacidades visuales y aumenta la capacidad de atención y los tiempos de reacción a estímulos en los niños. Las ventajas de su utilización suelen ser bien reconocidas: facilidad de obtener recursos educativos y de información, pertenecer a grupos para actividades específicas que son de su interés, o bien generar contenidos, explorar y expresarse en distintos campos, entre otras.…”
Section: Pediatría Prácticaunclassified
“…Kim, 2011;Shin & Jeong, 2018) . (Terras & Ramsay, 2016) , . (Lou, Shih, Liu, Guo, & Tseng, 2010), (Ahn, 2008) , .…”
Section: Tvmentioning
confidence: 99%